A COMPARATIVE CLINICAL STUDY OF VAMANA & VIRECHANA WITH AND WITHOUT SHILAJIT YOGA IN THE MANAGEMENT OF MADHUMEHA W.S.R. TO TYPE-2 DIABETES MELLITUS (AYUSHDHARA, 2017)
Diabetes Mellitus, a syndrome of disordered metabolism with multifactorial aetiology is characterized by chronic hyperglycaemia subsequently leading to long-term damage, dysfunction and multiple organ failure. Owing to the importance of disseminating the awareness, first National Ayurveda Day celebrated on 28th Oct. 2016, observed the theme as ‘Ayurveda for prevention and control of Diabetes. Madhumeha concedes 2 subtypes viz., Dhatukshayaja and Margavarodhaja. ‘Samshodhanam Akurvatam’ forms one of the important aetiological factors of Madhumeha which instigated in considering Panchakarma procedures of Vamana and Virechana karma for Shodhana particularly in Margavarodhaja madhumeha and, for a comprehensive management Shilajit Yoga is considered for Shamana therapy. Material and Methods: The study involved Group A (90 days): Vamana & Virechana (30 days) + Placebo (60 days). Group B (90 days): Vamana & Virechana (30 days) + Shilajit yoga (60 days). Dosage: 1 Cap. of 1000mg. Twice daily, Before food. Results: In placebo controlled Group-A, 6 (13.63%) got Controlled results, 10 (22.72%) got Marked Improvement, 24 (54.54%) got Moderate Improvement, 4 (9%) got Mild Improvement and in 4 patients there is No Change. In case of Drug trial (Shilajit Yoga) Group-B, 24 (50%) got Controlled results, 14 (29.1%) got Marked Improvement and 10 (20.8%) got Moderate Improvement. Discussion: Vamana acts on the basic pathology of Bahudravasleshma and Bahuabadhameda. Vamana and Virechana seems to reduce the insulin resistance, and Virechana must be increasing insulin secretion also. In contrast to Group A, ‘Shilajit yoga’ intervened in Group B appears to have substantial controlling effect on the blood sugar levels with its Extra pancreatic and Immunomodulatory effects, and probably through Pancreatotrophic action. Conclusion: The final result of the study supports the role of Shilajit followed by Shodana procedures as a safe and complete substitute to allopathic medication in the patients with an excess of about 50-100mg/dl of blood glucose levels above normal levels, in FBS and PPBS values.